The effect of fermenting seaweed extracts from the beach of Latakia with the biofertilizer EM1 on the growth of cucumber plants (height-leaves-flowers) - شعبان, حسين; هديل عراج (Latakia University Journal -Biological Sciences Series, 2025)
Seaweed clearly affected the growth of cucumber plants during all growth stages, and gave quick and clear results during the first weeks when fertilized with the extracts. The marine algae extracts were divided into three sections (algae extract after drying - algae extract after drying + EM1 - algae extract without drying + EM1), the extracts were applied to cucumber plants and compared with two groups, the first with chemical fertilizers (Urea 46%) and a second control group(Irrigated with water only). Algae extract after drying + EM1 gave the best results during the experiment period that extended to 6 weeks, where morphological measurements were taken (height_leaves_flowers), where the highest average length of the plant was recorded in the sixth week (157.66) cm, while the control recorded in the sixth week an average length of ( 79) cm. The average number of leaves in the sixth week was (73.66) leaves. The average number of leaves in the control in the sixth week was (42) leaves. As for the number of flowers, it recorded an average of (13) flowers in the fifth week, while the control recorded an average of (6) Flowers in the fourth week of the experiment.